Predictive value of post‐treatment C‐reactive protein‐to‐albumin ratio in locally advanced non–small cell lung cancer patients receiving durvalumab after chemoradiotherapy - Taisuke Araki; Kazunari Tateishi; Masamichi Komatsu; Kei Sonehara; Satoshi Wasamoto; Shigeru Koyama; Fumiaki Yoshiike; Mineyuki Hama; Kenichi Nishie; Daichi Kondo; Toshihiko Agatsuma; Akane Kato; et al. (Thoracic Cancer, 2022)
Abstract Backgrounds The PACIFIC trial established durvalumab consolidation therapy after concurrent chemoradiotherapy (CCRT) as the standard treatment for locally advanced non–small cell lung cancer (LA‐NSCLC). However, little is known about the predictive factors of durvalumab efficacy in this population. This study aimed to validate the predictive use of inflammation‐related parameters in patients with LA‐NSCLC treated with CCRT plus durvalumab. Methods We recruited 76 LA‐NSCLC patients who received CCRT followed by durvalumab from 10 Japanese institutions. The neutrophil‐to‐lymphocyte ratio (NLR), C‐reactive protein‐to‐albumin ratio (CAR), and prognostic nutrition index (PNI) were measured before (pre‐treatment) and 2 months after (post‐treatment) durvalumab induction. Cox proportional hazards analysis was used to examine prognostic factors associated with progression‐free survival (PFS) after durvalumab therapy. Results The median follow‐up time was 17 (range, 3.3–35.8) months. The median PFS and overall survival (OS) times were 26.1 and 33.7 months, respectively. Durvalumab was discontinued in 47 (61.8%) patients, with non‐infectious pneumonitis being the most common reason. Post‐treatment CAR (cutoff, 0.2) was a significant stratifying factor in survival comparison (<0.2 vs. ≥ 0.2, median PFS, not‐reached vs. 9.6 months. Log‐rank, p = 0.002). Multivariate analysis with a Cox proportional hazards model showed that post‐treatment CAR was an independent prognostic factor for PFS (hazard ratio, 3.16, p = 0.003). Conclusions This study suggests that post‐treatment CAR has predictive value for LA‐NSCLC patients treated with CCRT plus durvalumab consolidation therapy.